2017
DOI: 10.1016/j.intimp.2017.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Capsular specific IgM enhances complement-mediated phagocytosis and killing of Cryptococcus neoformans by methamphetamine-treated J774.16 macrophage-like cells

Abstract: Methamphetamine (METH) is a powerful and highly addictive stimulant that affects the central nervous system of users in the United States and worldwide, and its consumption is associated to the acquisition of HIV and AIDS-related infections. METH enhances cryptococcosis in mice, an opportunistic infection caused by the encapsulated fungus Cryptococcus neoformans. Due to its ability to survive within macrophages, C. neoformans is an ideal model to study pathogen-macrophage interactions. METH abrogates normal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Recent evidence supporting this possibility showed that METH mediates structural changes to the capsular composition (11) and inhibits complement-mediated phagocytosis (13) of C. neoformans. Interestingly, specific IgM to GXM enhances complement-mediated phagocytosis of the fungus (13), suggesting that the pentameric structure of this isotype may prevent METH-induced capsular modifications and positively influence the interaction of C. neoformans with complement receptors in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent evidence supporting this possibility showed that METH mediates structural changes to the capsular composition (11) and inhibits complement-mediated phagocytosis (13) of C. neoformans. Interestingly, specific IgM to GXM enhances complement-mediated phagocytosis of the fungus (13), suggesting that the pentameric structure of this isotype may prevent METH-induced capsular modifications and positively influence the interaction of C. neoformans with complement receptors in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis assay. Macrophage-or microglia-like cells were incubated in 96-well microtiter plates (Corning) in the absence or presence of METH (25 or 50 M; Sigma) for 2 h. Cytochalasin D (25 M; Sigma) was used as a positive control because it potently inhibits actin polymerization and phagocytosis (13,15). Monolayers of J774.16 or NR-9640 cells were washed thrice with PBS, and feeding medium (13) supplemented with gamma interferon (IFN-␥; 100 U/ml) and bacterial lipopolysaccharide (LPS; 1 g/ml) was added, followed by the addition of preincubated cryptococci with MAb 18B7 (anti-cryptococcal GXM IgG1 generated and generously provided by Arturo Casadevall; 2 g/ml) for 1 h, in a macrophage/ microglia (10 5 cells):yeast/latex bead (Thermo Fisher) (10 6 cells) ratio of 1:10.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations